Lean Companies Employed Assembly Workers Train with New Approches (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
LM has proven itself the production system that enhances shop floor efficiency. Furthermore, the current environment for production firms is accelerating the pace at which LM is implemented. The manufacture of lean is not easy to introduce. It is constant and complex activity. Assembly workers in production processes are the core of lean manufacturing activity. Training is known as vehicle to aid the implementation process. While the importance of training is known so far, there are only a few options for organizing effective training. The results of the survey of questions conducted inside UK manufacturing companies are examined. This article illustrates the definition of lean production and worker requirements in lean environment.